IDENTIFIKASI KRIPTOSPORIDIOSIS DI PASIEN ANAK HIV DENGAN DIARE KRONIS DI RUANG GASTRO ANAK - Jusak Nugraha; Febtarini Rahmawati; Dominicus Husada (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Based on the results of overseas researchers, Cryptosporidiosis occurs in immunosuppressive cases with chronic diarrhoea. In this study the researchers would like to know exactly whether that Cryptosporidiosis occurs also in paediatric HIV patients. The latest data show that the incidence of opportunistic infection is characterized by persistent diarrhoea and severe malnutrition as a complication of the paediatric HIV-infected patients is increasing. The objects of the research were fifteen paediatric HIV-infected patients which treated at the Paediatric Gastro Ward of Dr. Soetomo Hospital Surabaya due to persistent diarrhoea. Paediatric patients were less than five years old, suffered persistent diarrhoea more than two weeks with severe malnutrition. Stool specimens were transported using 10% formalin. The stool suspension was filtered, and distilled water was added followed by centrifugation (sedimentation method). The precipitate material was placed on a glass object and dried, and then fixed by methanol and stained with Acid Fast Staining and trichrome staining. The protozoa Cryptosporidium spp. was observed under a binocular microscope with 100× magnification (immersion oil) objective. The result was confirmed as positive if a red spherical or oval formation of oocyste of 4–6 micron appeared. Sixty percent of the 15 paediatric HIV-infected patients with chronic diarrhoea showed positive cryptosporidiosis. Cryptosporidiosis is one of the opportunistic infections resulting in chronic diarrhoea in paediatric HIV-infected patients. The results of the present research indicate that the enteric parasite Cryptosporidium spp. was the main cause of persistent diarrhoea in paediatric HIV-infected patients